Tipologi pengajaran dan pendidikan Islam di Banten dalam pengaruh tokoh ulama abad 19-20 - Murniasih, Eri; Anshori, Irfan (LPPM Universitas Ibn Khaldun, Bogor, 2024)
Banten has a lot of culture and culture and is synonymous with the sultanate, so it has many Islamic educational institutions and centers of Islamic government. This research aims to describe the history of the development of Islamic education in Banten in the 19th and 20th centuries. This research was carried out using the literature study method through the approach of figures (ulama) who were influential in spreading Islam. Judging from the struggle and contribution to education and organizations in the Banten region. The research results show that Banten's progress cannot be separated from the disciplined work of its ulama in aspects of Islamic science. Four models or patterns of Islamic religious education and teaching institutions are known and running from time to time in Banten, namely Islamic religious education in Islamic boarding schools, madrasas, majlis ta'lim, and religious education in public schools. The progress of Islam in Banten was also supported by the establishment of Islamic organizations such as Mathla'ul Anwar, Al-Khairiyah, and Mathla’ul Anwar Linahdlatil Ulama (MALNU) which became the basis of Islamic power in Banten. Abstrak Banten memiliki banyak kultur, budaya serta identik dengan wilayah kesultanan sehingga banyak mencetak lembaga pendidikan keislaman dan pusat pemerintahan Islam. Tujuan penelitian ini menggambarkan sejarah perkembangan pendidikan Islam di Banten abad 19-20. Penelitian ini dilakukan dengan metode studi kepustakaan melalui pendekatan tokoh (ulama) yang berpengaruh dalam menyebarkan Islam. Dilihat dari perjuangan serta kontribusinya dalam pendidikan, dan organisasi yang ada di wilayah Banten. Hasil Penelitian menunjukkan bahwa kemajuan Banten tidak terlepas dari kiprah para ulamanya yang disiplin dalam aspek keilmuan Islam. Dan terdapat empat model atau pola institusi pendidikan dan pengajaran agama Islam yang dikenal dan berjalan dari waktu ke waktu di Banten yaitu pendidikan agama Islam di pondok pesantren, madrasah, majelis ta’lim dan pendidikan agama di sekolah umum. Kemajuan Islam di Banten juga di dukung dengan didirikannya organisasi Islam seperti Mathla’ul Anwar, Perguruan Al-Khairiyah serta Mathla’ul Anwar Linahdlatil Ulama (MALNU) yang menjadi basis kekuatan Islam di Banten.